Corruption v democracy - part three: The 2024 elections - Lewis, David (New Agenda: SA Journal of Social and Economic Policy, 2024)
For the first time since 1994 the ANC’s share of the national vote has fallen below 50%, declining from 57.5% in 2019 to 40.2% in 2024. As significant, the provincial shares in Gauteng and KwaZulu-Natal (KZN) provinces fell well below 50%, with the recently formed uMkhonto weSizwe (MK) party, led by none other than Jacob Zuma, capturing 45.35% share of the KZN vote and the ANC share dropping from 54.2% to a paltry 16.9%. In Gauteng the ANC’s share of the vote declined from 50.2% to 34.6%. The Democratic Alliance’s (DA’s) share remained approximately stable at 27.5% in Gauteng and 21.8% nationally.The ANC leadership has publicly acknowledged that corruption and, associated with it, extremely poor delivery of social services (largely a provincial and local government responsibility), is a leading cause of the electorate’s devastating judgment. The upshot is that in the national government and in three provinces (Gauteng, KZN and the Northern Cape), the ANC has had to form or constitute part of a coalition government to continue to participate in a majority government.